Gold Micropetals Self‐Assembled by Shadow‐Sphere Lithography for Optofluidic Control (Adv. Mater. Interfaces 18/2022). Issue 18 (22nd June 2022) - Namura, Kyoko; Hanai, Shunya; Kondo, Shuji; Kumar, Samir; Suzuki, Motofumi
Abstract : Petal‐Like Gold Microstructures Petal‐like gold microstructures with optimum optical absorption distribution are successfully self‐assembled via the shadow‐sphere lithography technique as reported in article number 2200200 by Kyoko Namura, Shunya Hanai, and co‐workers. Microbubble generation and microfluidic pumping are realized by homogeneous laser beam irradiation on the gold micropetal because of its photothermal property.